The problem child - Buckley, Michael; Ferguson, Peter, 1968- (New York : Amulet Books, 2007)
With the help of a long lost relative, and a little magic, Sabrina Grimm and her sister Daphne try to find out who has kidnapped their parents and rescue them.
Keywords: Characters in literature -- Juvenile fiction; Sisters -- Juvenile fiction; Grandmothers -- Juvenile fiction; Characters in literature -- Fiction; Sisters -- Fiction; Grandmothers -- Fiction; Mystery and detective stories; Sisters -- Fiction; Parents -- Fiction; Grandmothers -- Fiction; Kidnapping -- Fiction; Characters and characteristics in literature -- Fiction; Mystery fiction; Mystery fiction; Fantasy fiction